A influência dos fatores de risco da doença renal crônica no crescimento estatural de crianças em tratamento conservador - Zuza, Yara Aparecida Cunha Ferreira (2017)
Short stature in children with chronic kidney disease (CKD) has a multifactorial etiology, high prevalence, and high morbidity and mortality, which becomes more frequent with the progressive reduction of the glomerular filtration rate (GFR). The objective of this study was to analyze risk factors associated with short stature at both the beginning and end of conservative treatment. This is a retrospective cohort study, in which the medical records of patients with CKD, aged less than 13 years at the beginning of follow-up, were evaluated between 1999 and 2015. Of the 71 patients examined, 60.6% were male and the average follow-up duration was 62.4 ± 49 months. Age, height, presence of systemic blood hypertension (SBH), anemia, metabolic acidosis, proteinuria, and estimated GFR were evaluated (Schwartz's formula). Patients were divided into groups based on initial stature (normal or low) and initial GFR (< or ≥30 mL/min/1.73m2). The Chi-square test, paired t-test, Kaplan-Meier curves, and multivariate Cox regression models were used in the statistical analysis. Twenty-five patients displayed short stature at the beginning of the study. Acidosis was associated with short stature at the start of follow-up, while GFR and anemia were associated with short stature at the end of follow-up. There was a significant reduction in the number of hypertensive patients in the GRF initial ≥ 30ml/min/1,73m2 and normal initial stature groups, but SBH was not associated with short stature. Creatinine doubling, considered a marker of progression of renal disease, was the most significant independent factor for short stature (r = 10.3; P <0.05), regardless of initial GFR (r = 2.25, P <0.05) or acidosis (r = 3.84, P 0.05). Despite the clinical control of children with CKD receiving conservative treatment, there was a progression in the number of cases of short stature during follow-up, probably due to late referral to our service and the progressive reduction of renal function. The risk factors studied are differently associated with short stature at the beginning and ate the end of monitoring of children in conservative treatment.